Sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and preparation method of sulfur-modified modified electrode

By deposition of Cu2O-Cu2S-Cu(V)/CuxO-CuxS/CM core-shell structure catalyst using cyclic voltage pulses and constant voltage method on the surface of the copper substrate, the problem of sulfur easy dissolution during the electrochemical reduction of carbon dioxide is solved, and the stability and selectivity of the catalyst are significantly improved, achieving efficient CO2 conversion and improvement of reaction efficiency.

CN119710770AActive Publication Date: 2025-03-28DALIAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411860437.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In the prior art, sulfur is easily soluble during the electrochemical reduction of carbon dioxide, affecting the stability and selectivity of the catalyst, resulting in unstable product selectivity of copper-based materials, and hindering the practicalization of electrochemical ECR-CO2 technology.

Method used

The Cu2O-Cu2S-Cu(V)/CuxO-CuxS/CM core-shell structure catalyst was deposited and grown on the surface of the copper substrate by cyclic voltage pulse and constant voltage method, and the stability and selectivity of the catalyst were improved by electrochemical potential reconstruction technology.

Benefits of technology

It significantly improves the stability and selectivity of the catalyst, enhances the efficient conversion of CO2 to HCOOH, inhibits the H2 and CO pathways, and improves the efficiency of electrochemical CO2 reduction reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710770A_ABST
    Figure CN119710770A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-modified electrode for electrochemical reduction of carbon dioxide and a preparation method, and relates to the field of sulfur-modified electrodes, and the preparation method comprises the step of growing a Cu2O-Cu2S-Cu (V) / CuxO-CuxS / CM catalyst with a core-shell structure on a copper substrate through in-situ deposition on the surface of a substrate layer of the copper substrate through electrochemical pulse deposition and electrochemical constant potential deposition reconstruction technologies. In the growth process, CuxS-CuxO is prepared on the surface of the substrate through pulse deposition; and then, by utilizing electrochemical constant potential structure reconstruction, CuxO and CuxS on the surface layer of the catalyst are reconstructed and reduced, Cu2O-Cu2S-Cu (V) grows on the surface, and a sulfur modified electrode is formed. The sulfur modified electrode is prepared by coupling pulse electrodeposition with constant potential deposition reconstruction, the preparation method is simple, the raw material source is wide, the developed electrode has good selectivity and high catalytic activity and stability, and the solid, liquid and gas three-phase interface area is enlarged through structure reconstruction, so that the catalytic activity of the electrode is improved. And the electrocatalyst can have more active sites and larger specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sulfur-modified electrodes, and in particular to a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and a preparation method thereof. Background Art

[0002] Against the backdrop of increasingly severe global climate change, carbon dioxide (CO2), as the main greenhouse gas, has become an important topic of scientific research in terms of emission reduction and conversion. In order to meet this challenge, researchers are constantly exploring innovative methods to achieve efficient conversion and utilization of CO2. Among them, electrochemical reduction of carbon dioxide (ECR-CO2) technology has received widespread attention as a promising solution. ECR-CO2 technology uses electrical energy to convert CO2 into valuable chemicals such as methanol, ethanol, carbon monoxide, etc. This process not only reduces CO2 emissions, but also produces renewable fuels and raw materials. This technology offers potential for widespread application in the fields of addressing climate change, energy security, and sustainable chemistry.

[0003] Copper-based materials show unique advantages in the electrochemical ECR-CO2 conversion process, especially their ability to bind key reaction intermediates (such as *COOH, *CO, *CHO and *COH). The core-shell structure formed by the present invention can not only effectively promote the adsorption of *COOH intermediates, but also improve the adsorption efficiency of copper catalysts. x The S catalyst has a higher binding energy with *OCHO due to the stabilizing effect of the negatively charged S atom. x S promotes the dissociation of H2O into adsorbed H, and the two synergistically reduce the formation barrier of formic acid, thereby promoting the efficient conversion of CO2 to HCOOH, and can significantly inhibit the H2 and CO pathways. However, a key challenge lies in the stability and selectivity of the catalyst: under cathode conditions, sulfur is easily dissolved in the electrolyte, a property that directly affects the composition stability and structural integrity of the catalyst, and the selectivity of the product of copper-based materials is unstable, which becomes a major obstacle to its practical application and commercialization. Therefore, exploring methods to improve sulfur stability or developing alternative catalyst design strategies is of great significance to promoting the practical application of electrochemical ECR-CO2 technology.

[0004] To this end, we provide a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and a preparation method to solve the above problems. Summary of the invention

[0005] In view of the problems existing in the above-mentioned prior art, the present invention provides a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and a preparation method thereof, so as to solve the problem that the prior art is still insufficient in methods for improving sulfur stability or developing alternative catalyst design strategies.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts a sulfur-modified electrode for electrochemical reduction of carbon dioxide, which is deposited and reconstructed to grow Cu2O-Cu2S-Cu(V) / Cu on the surface of the base layer of the copper base by electrochemical deposition and electrochemical reduction technology. x O-Cu x S / CM catalyst;

[0007] A sulfur-modified electrode for electrochemical reduction of carbon dioxide, characterized in that:

[0008] The core-shell structure Cu2O-Cu2S-Cu(V) / Cu was in situ deposited and grown on the surface of the copper substrate by electrochemical pulse deposition and electrochemical constant potential deposition reconstruction technology. x O-Cu x S / CM catalyst;

[0009] During the growth process, Cu is first deposited on the substrate surface. x O-Cu x S;

[0010] Then, the electrochemical constant potential deposition reconstruction technique was used to deposit and reconstruct the prepared catalyst, and the Cu x O and Cu x S is reduced and reconstructed, and Cu2O-Cu2S grows on the surface to form a sulfur-modified electrode.

[0011] A method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide, characterized in that the method comprises the following steps:

[0012] S1: soak the copper mesh, copper foam and copper plate substrate in water, 25% hydrochloric acid, ethanol or acetone in turn, clean them by ultrasonic cleaning in an ultrasonic cleaning machine, and then clean and dry them for later use;

[0013] S2: a mixed solution of bicarbonate, carbonate and sodium sulfide is prepared as an electrolyte, and stirred for 20 minutes under a magnetic stirrer to fully mix, wherein the concentration of sodium bicarbonate and carbonate is 0.1M to 1M, preferably 0.1M to 0.5M; the concentration of sulfur is 0.3mM to 2.0mM, preferably 0.5mM to 1mM;

[0014] S3: Under the protection of inert gas, the oxidation potential Ea of the cyclic voltage pulse is -0.2V~-0.6V; the reduction potential Ec is -1.2V~-0.6V;

[0015] The absolute value of the oxidation potential is always set smaller than the absolute value of the reduction potential;

[0016] The oxidation time Δta is 1 to 5 seconds, preferably 2 to 4 seconds;

[0017] The reduction time Δtc is 2 to 8 seconds, preferably 4 to 8 seconds;

[0018] The number of cycles is 50 to 400, preferably 100 to 200;

[0019] S4: The electrode prepared in step S3 is placed under the protection of an inert gas and reconstructed by electrochemical constant potential in the same electrolyte to reconstruct the surface of the substrate layer by electrodeposition of the catalyst;

[0020] S5: Rinse the electrode prepared in S4 and dry it in a vacuum drying oven at 40-60° C. to prepare a sulfur-modified electrode.

[0021] The method for preparing a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide is characterized in that: the concentration of the sodium bicarbonate salt and the carbonate is 0.1M to 1M, preferably 0.1M to 0.5M; the concentration of the sulfur is 0.3mM to 2mM, preferably 0.5mM to 1mM;.

[0022] The method for preparing a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide is characterized in that: the oxidation time Δta in S3 is 1 to 10 seconds, preferably 2 to 4 seconds;

[0023] The reduction time Δtc is 2 to 8 seconds, preferably 4 to 8 seconds; the number of cycles is 50 to 400 times, preferably 100 to 200 times.

[0024] The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide is characterized in that the molar ratio of the sodium bicarbonate salt or carbonate to sodium sulfide is 117:1 to 200:1, and the preferred molar ratio is 150:1 to 180:1.

[0025] The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide is characterized in that the sodium bicarbonate salt and carbonate of the electrolyte solution of the cyclic voltage pulse are one or more of KHCO3, NaHCO3, Na2CO3, and K2CO3.

[0026] The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide is characterized in that the concentration of the electrolyte is 0.1M to 1M, preferably 0.1M to 0.5M.

[0027] The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide is characterized in that the constant potential method uses a constant voltage method.

[0028] The sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and the preparation method are characterized in that the voltage used in the constant voltage method is set to -2.0V to -1.0V, and the deposition time is 800 to 2000 seconds.

[0029] As a further optimization of the above scheme, the concentration of sodium bicarbonate and carbonate is 0.1M to 0.5M;

[0030] The concentration of the sulfide is 0.5 mM to 1.0 mM.

[0031] As a further optimization of the above scheme, the oxidation time Δta in S3 is 2 to 4 seconds;

[0032] The reduction time Δtc is 4 to 8 seconds;

[0033] The number of cycles is 100 to 200 times.

[0034] As a further optimization of the above scheme, the molar ratio of the sodium bicarbonate salt or carbonate to sodium sulfide is 150:1 to 180:1.

[0035] As a further optimization of the above scheme, the sodium bicarbonate salt and carbonate of the electrolyte solution of the cyclic voltage pulse are one or more of KHCO3, NaHCO3, Na2CO3, and K2CO3;

[0036] As a further optimization of the above solution, the concentration of the electrolyte is 0.1M to 0.5M.

[0037] As a further optimization of the above scheme, the voltage used in the constant voltage method is set to -2.0V to -0.5V, and the deposition time is 800 to 2000 seconds.

[0038] The sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and the preparation method of the present invention have the following beneficial effects:

[0039] The present invention focuses on the performance optimization strategy of copper-based metal catalysts and deeply studies the ways to enhance catalytic performance by regulating their crystal surface characteristics and grain boundary structure. The electrocatalyst is prepared by using a cyclic pulse voltage combined with a constant voltage method to form a core-shell structure, and a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide is prepared.

[0040] The preparation method of the present invention is simple, the raw material sources are wide, and it has high catalytic activity and stability. It only needs to be prepared by cyclic pulse voltage and constant pressure method in alkaline and sulfur-containing electrolytes. By expanding the solid-liquid-gas three-phase interface area, the electrocatalyst can have more active sites and a larger specific surface area.

[0041] At the interface between solid, liquid and gas phases, CO2 undergoes a reduction reaction (ECR-CO2), and the core-shell structure undergoes an instant surface structural transformation, which not only accelerates the generation of the key intermediate *OCHO, but also effectively blocks the competitive adsorption of *H and *COOH. This mechanism significantly promotes the selectivity of the electrochemical CO2 reduction reaction (ECR-CO2) to formic acid, thereby achieving a more efficient catalytic efficiency.

[0042] Compared with conventional electrochemical deposition, the copper mesh surface can be modified innovatively by combining cyclic pulse voltage with constant voltage in a sulfur-rich electrolyte solution. This method can not only continuously expose new interfaces, but also effectively purify the substrate. The constant voltage causes the sulfur ions in the electrolyte to undergo an electrochemical reduction reaction on the surface of the copper mesh, firmly adhere to the surface of the copper mesh, and reduce the copper oxide to cuprous oxide. In this process, the constant potential ensures the stability and uniformity of the deposition rate, avoiding the problem of uneven quality or shedding of the deposited layer due to potential fluctuations.

[0043] This preparation method is simple and efficient, with abundant raw material resources, and the obtained electrocatalyst exhibits excellent catalytic activity and stability. Through cyclic pulse voltage and constant pressure treatment in an alkaline sulfur-containing electrolyte, the catalyst can be prompted to form abundant active sites and an expanded specific surface area. This catalyst not only effectively inhibits the hydrogen evolution side reaction, but also significantly improves the selectivity of formic acid production. The overall preparation process is fast and environmentally friendly, with low energy consumption and no pollution, and is an ideal electrocatalyst preparation solution.

[0044] With reference to the following description and drawings, a specific embodiment of the present invention is disclosed in detail, indicating the manner in which the principles of the present invention can be adopted. It should be understood that the scope of the embodiments of the present invention is not limited thereby, and within the spirit and scope of the appended claims, the embodiments of the present invention include many changes, modifications and equivalents. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 X-ray energy dispersive spectrometer (EDS) characterization of the sulfur-modified electrode material for electrochemical reduction of carbon dioxide of the present invention;

[0046] Figure 2 X-ray energy dispersive spectrometer (EDS) characterization of the sulfur-modified electrode material for electrochemical reduction of carbon dioxide of the present invention;

[0047] Figure 3 X-ray energy dispersive spectrometer (EDS) characterization of the sulfur-modified electrode material for electrochemical reduction of carbon dioxide of the present invention;

[0048] Figure 4Scanning electron microscopy (SEM) characterization of the sulfur-modified electrode material for electrochemical reduction of carbon dioxide of the present invention;

[0049] Figure 5 Scanning electron microscopy (SEM) characterization of the sulfur-modified electrode material for electrochemical reduction of carbon dioxide of the present invention;

[0050] Figure 6 The present invention is a flow chart of the preparation method of the sulfur-modified electrode for electrochemical reduction of carbon dioxide. DETAILED DESCRIPTION

[0051] Please refer to the instruction manual Figures 1 to 4 The present invention provides a technical solution: a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and a preparation method thereof.

[0052] Electrodeposition technology is an efficient, environmentally friendly and flexible preparation method suitable for the preparation and modification of catalysts. This technology can accurately regulate the morphology, structure and performance of Cu catalysts by controlling electrodeposition parameters such as current, voltage, electrolyte composition, temperature and deposition time. The adjustment of these parameters will directly affect the deposition rate, grain size and surface morphology of the catalyst, and thus affect its catalytic activity and selectivity. By optimizing these parameters, the performance of the catalyst can be regulated, so that it can show excellent performance in electrocatalytic carbon dioxide reduction.

[0053] The present invention uses a copper substrate to carry out innovative modification treatment of the copper substrate by implementing a cyclic voltage pulse combined with a constant voltage method in a sulfur-rich electrolyte solution, and successfully prepares a high-efficiency copper-based electrocatalyst. The surface is deposited and grown on the surface of the substrate layer by electrochemical deposition and electrochemical reduction technology. x O-Cu x S / CM core-shell structure; during the growth process, Cu is first deposited on the substrate surface x S-Cu x O; then, the electrochemical reduction technique was used to reconstruct the prepared catalyst, and the copper oxide and Cu x S is reduced and reconstructed, allowing the substrate to continue to grow Cu2S-Cu2O, and a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide is prepared. Through chemical and electrochemical reduction technology, the structure of the catalyst surface is tailored, and the heterogeneous metal is induced to promote surface reconstruction. The outer layer of Cu2O helps to improve the activity and selectivity of the catalyst. xS vacancies lead to more electrons being donated to *OCHO, thus improving the selectivity of formic acid; the catalyst surface reconstruction is achieved by using cyclic pulse technology and electrochemical reduction technology to adjust the number and proportion of active sites on the catalyst surface, or by introducing a small amount of functional modification layers and functional groups that can bond with C or O atoms on the catalyst surface. These functional modification layers have the potential to form chemical bonds with the intermediates of the reduction reaction (such as *COOH), thereby changing their adsorption and desorption strengths, and ultimately achieving the goal of improving the selectivity of the reduction products. During the cyclic pulse voltage process, not only the film structure and morphology can be precisely controlled, but the substrate can also be effectively purified. Even when faced with a non-high-purity Cu metal substrate, it can break through the limitations of long-term deposition and high-concentration precursors, ensuring continuous optimization of catalyst performance. Constant pressure allows the copper oxide and Cu on the surface layer to react with the copper oxide and Cu x S is reduced and reconstructed to form a Cu x S-Cu2O modified covering layer. The constant potential ensures the stability and uniformity of the deposition rate, avoiding the problem of uneven quality or shedding of the deposition layer caused by potential fluctuations. The electrocatalyst prepared by the cyclic voltage pulse and constant voltage method showed significant effects in the carbon dioxide electroreduction process, effectively curbing the occurrence of hydrogen evolution side reactions and significantly improving the selectivity of formic acid products, thereby optimizing the efficiency and product distribution of the catalytic reaction.

[0054] The electrode is deposited and grown on the surface of the substrate by pulse electrochemical deposition. x S-Cu x O / substrate; constant potential method makes Cu x S-Cu x O / substrate layer undergoes electrochemical reduction and reconstruction, allowing the substrate to continue to grow Cu2O-Cu2S-Cu(V) / Cu x O-Cu x S / CM core-shell structure. The electrocatalyst is prepared according to the following steps:

[0055] S1: soak the copper mesh, copper foam and copper plate substrate in water, 25% hydrochloric acid, ethanol or acetone in turn, clean them by ultrasonic cleaning in an ultrasonic cleaning machine, and then clean and dry them for later use;

[0056] S2: a mixed solution of bicarbonate, carbonate and sodium sulfide is prepared as an electrolyte, and stirred for 20 minutes under a magnetic stirrer to fully mix, wherein the concentration of sodium bicarbonate and carbonate is 0.1M to 1M, preferably 0.1M to 0.5M; the concentration of sulfur is 0.3mM to 2.0mM, preferably 0.5mM to 1mM;

[0057] S3: Under the protection of inert gas, the oxidation potential Ea of the cyclic voltage pulse is -0.2V~-0.6V; the reduction potential Ec is -1.2V~-0.6V;

[0058] The absolute value of the oxidation potential is always set smaller than the absolute value of the reduction potential;

[0059] The oxidation time Δta is 1 to 5 seconds, preferably 2 to 4 seconds;

[0060] The reduction time Δtc is 2 to 8 seconds, preferably 4 to 8 seconds;

[0061] The number of cycles is 50 to 400, preferably 100 to 200;

[0062] S4: The electrode prepared in step S3 is placed under the protection of an inert gas and reconstructed by electrochemical constant potential in the same electrolyte to reconstruct the surface of the substrate layer by electrodeposition of the catalyst;

[0063] S5: The electrode prepared in S4 is rinsed clean and dried in a vacuum drying oven at 40-60° C. to prepare a sulfur-modified electrode.

[0064] The electrocatalyst can act as a cathode catalyst in the electrochemical reduction reaction of carbon dioxide.

[0065] Example 1

[0066] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.85mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 100. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 1200 seconds. The prepared electrocatalyst is dried in a vacuum drying oven at room temperature to prevent oxidation of the catalyst, thereby preparing a sulfur-modified modified electrode material catalyst for electrochemical reduction of carbon dioxide.

[0067] Example 2

[0068] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.35mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 100 times. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 1200 seconds. The prepared electrocatalyst is dried at room temperature in a vacuum drying oven to prevent oxidation of the catalyst, and the catalyst is prepared.

[0069] Example 3

[0070] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.65mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 100 times. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 1200 seconds. The prepared electrocatalyst is dried at room temperature in a vacuum drying oven to prevent oxidation of the catalyst, and the catalyst is prepared.

[0071] Example 4

[0072] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 1mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 100 times. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 1200 seconds. The prepared electrocatalyst is dried at room temperature in a vacuum drying oven to prevent oxidation of the catalyst, and the catalyst is prepared.

[0073] Example 5

[0074] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.85mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 50 times. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 1200 seconds. The prepared electrocatalyst is dried in a vacuum drying oven at room temperature to prevent oxidation of the catalyst, thereby preparing a sulfur-modified modified electrode material catalyst for electrochemical reduction of carbon dioxide.

[0075] Example 6

[0076] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.85mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 150 times. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 1200 seconds. The prepared electrocatalyst is dried in a vacuum drying oven at room temperature to prevent oxidation of the catalyst, thereby preparing a sulfur-modified modified electrode material catalyst for electrochemical reduction of carbon dioxide.

[0077] Example 7

[0078] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.85mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 100. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 800 seconds. The prepared electrocatalyst is dried in a vacuum drying oven at room temperature to prevent oxidation of the catalyst, thereby preparing a sulfur-modified modified electrode material catalyst for electrochemical reduction of carbon dioxide.

[0079] Example 8

[0080] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.85mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 100. After the cyclic pulse ends, constant voltage reduction is immediately performed, the reduction voltage is set to -1.5V, and the time is 1600 seconds. The prepared electrocatalyst is dried in a vacuum drying oven at room temperature to prevent oxidation of the catalyst, thereby preparing a sulfur-modified modified electrode material catalyst for electrochemical reduction of carbon dioxide.

[0081] Comparative Example 1

[0082] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, and then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.85mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for cyclic voltage pulse, setting the voltage Ea = -0.2V, the time Δta = 2 seconds; setting the potential Ec = -0.6V, the time Δtc = 4 seconds, and the number of cycles is 100 times. After the cyclic pulse is completed, the prepared electrocatalyst is dried at room temperature in a vacuum drying oven to prevent the catalyst from oxidation, and the catalyst is prepared.

[0083] Comparative Example 2

[0084] The copper mesh substrate layer is soaked in hydrochloric acid, water, ethanol or acetone with a molar concentration of 2 to 5 mol / L in turn, ultrasonicated in an ultrasonic cleaning machine for 15 minutes, and then cleaned and dried for use; a certain amount of mixed solution of sodium bicarbonate and sodium sulfide is prepared, the concentration of sodium bicarbonate is 0.1M, and the concentration of sodium sulfide is 0.85mM, and stirred with a magnetic stirrer for 20 minutes to fully mix. Under the protection of inert gas, at room temperature, using Ag / AgCl electrode as a reference electrode, the treated copper mesh substrate is placed in the mixed solution for constant voltage reduction, the reduction voltage is set to -1.5V, and the time is 1600 seconds. The prepared electrocatalyst is dried at room temperature in a vacuum drying oven to prevent oxidation of the catalyst, and a sulfur-modified modified electrode material catalyst for electrochemical reduction of carbon dioxide is prepared.

[0085] Table 1 Distribution of reduction products of Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, Comparative Example 1 and Comparative Example 2

[0086]

[0087]

[0088] The prepared electrocatalyst was used as the cathode of the electrochemical catalytic reduction of carbon dioxide reaction system. The experiment used a three-electrode system for electrochemical testing. The prepared 1cm×1cm electrode material was used as the working electrode, the Ag / AgCl reference electrode was used as the reference electrode, and the 1cm 2 A platinum electrode was used as the counter electrode, the cathode chamber was 65 mL of 0.1 M NaHCO3 solution, and the anode chamber was 65 mL of 0.1 M NaHCO3 solution. During the electrocatalytic reduction of CO2 reaction, the CO2 flow rate was set to 50 mL / min; the catalytic reduction product was detected every 15 minutes.

[0089] Specifically, the difference in the distribution of reduction products between Example 1 and Example 2, and Example 3 and Example 4 in Table 1 is that the concentration of sodium sulfide during electrodeposition is different. When the concentration of sodium sulfide in Example 1 is 0.85 mM, the maximum Faraday efficiency of generating formic acid at -1.9 V is 88.54%, and the Faraday efficiency of hydrogen is 20.98%. When the concentration of sodium sulfide in Example 2 is 0.35 mM, the maximum Faraday efficiency of generating formic acid at -1.9 V is 79.53%, and the Faraday efficiency of hydrogen is 25.16%. When the concentration of sodium sulfide in Example 3 is 0.65 mM, the maximum Faraday efficiency of generating formic acid at -1.9 V is 82.97%, and the Faraday efficiency of hydrogen is 24.38%. When the concentration of sodium sulfide in Example 4 is 1 mM, the maximum Faraday efficiency of generating formic acid at -1.9 V is 67.83%, and the Faraday efficiency of hydrogen is 35.31%. Overall, the Faraday efficiency of formic acid shows a trend of first increasing and then decreasing with the concentration of sodium sulfide, and almost no other by-products are detected except hydrogen. The Faraday efficiency of formic acid is the highest at -1.9V. When the concentration of sodium sulfide is 0.85mM, formic acid has the highest Faraday efficiency of 88.54%, and side reactions such as hydrogen evolution are weakened. This shows that at -1.9V and the concentration of sodium sulfide is 0.85mM, the active sites provided by the core-shell structure on the surface of the copper substrate can adsorb more CO2. The S vacancies formed on the surface cause the Cu site to transfer more electrons, improve its selectivity, and then expand the three-phase interface area, accelerate the formation of the key intermediate *OCHO, effectively regulate the product selectivity and promote the conversion of CO2 to formic acid.

[0090] Specifically, the distribution of the reduction products of Example 1, Example 5 and Example 6 in Table 1 differs in that the number of cycles during cyclic pulse deposition is different. When the number of cycles during cyclic pulse deposition of Example 1 is 100, the highest Faraday efficiency for generating formic acid at -1.9V is 88.54%, and the Faraday efficiency for hydrogen is 20.98%. When the number of cycles during cyclic pulse deposition of Example 5 is 50, the highest Faraday efficiency for generating formic acid at -1.9V is 67.25%, and the Faraday efficiency for hydrogen is 26.33%. When the number of cycles during cyclic pulse deposition of Example 6 is 150, the highest Faraday efficiency for generating formic acid at -1.9V is 60.32%, and the Faraday efficiency for hydrogen is 35.32%. By comparison, it is found that the Faraday efficiency of formic acid is the highest when the number of cycles is 100. This indicates that the Cu that failed to fully react in the first step x S-Cu x O structure, resulting in the failure to remove the Cu x O and Cu x S was reconstructed and not reduced, and a good Cu2O-Cu2S-Cu(V) / Cu x O-Cux S / CM core-shell structure catalyst. Affects the selectivity of the catalyst for formic acid production.

[0091] Specifically, the difference in the distribution of reduction products of Example 1, Example 7 and Example 8 in Table 1 is that the time of constant potential reduction is different. When the time of applying the constant potential voltage in Example 1 is 1200 seconds, the maximum Faraday efficiency of generating formic acid at -1.9V is 88.54%, and the Faraday efficiency of hydrogen is 20.98%. When the time of applying the constant potential voltage in Example 7 is 800 seconds, the maximum Faraday efficiency of generating formic acid at -1.9V is 68.22%, and the Faraday efficiency of hydrogen is 28.38%. When the time of applying the constant potential voltage in Example 8 is 1600 seconds, the maximum Faraday efficiency of generating formic acid at -1.9V is 48.36%, and the Faraday efficiency of hydrogen is 45.63%. By comparison, when the time of applying the constant potential voltage is 1200 seconds, the Faraday efficiency of formic acid is the highest. This shows that in the first step of preparing Cu x S-Cu x O structure, the optimal time for the second step of electrochemical constant potential reconstruction is 1200 seconds, and a relatively complete core-shell structure is formed on the surface of the copper substrate, which provides more active sites for the adsorption and dissociation of CO2 and helps to convert carbon dioxide into formic acid.

[0092] Specifically, the difference in the distribution of reduction products between Example 1 and Comparative Example 1 in Table 1 is that during electrodeposition, the constant potential method is not added in Comparative Example 1 relative to Example 1. The highest Faraday efficiency of formic acid generated at -1.9V in Example 1 is 88.54%, and the Faraday efficiency of hydrogen is 20.98%. In contrast, the highest Faraday efficiency of formic acid generated at -1.9V in Example 2 is 79.53%, and the Faraday efficiency of hydrogen is 25.16%. The comparison proves that the lack of the constant pressure method fails to form a complete core-shell structure. The S ions in the solution cannot be reduced to the surface of the copper substrate layer, and the Faraday efficiency of formic acid on the sulfur-modified Cu2O electrocatalyst is highly dependent on the crystal plane of Cu2O. The lack of a constant pressure method makes it impossible to reduce the copper oxide and Cu x S is reduced and reconstructed, and Cu cannot be obtained x O-Cu x S / Cu2O-Cu2S-Cu(V) core-shell structure. When the number of active sites decreases, its overall catalytic activity will be weakened accordingly. At the same time, the proportion of edge active sites decreases, which also leads to a decrease in the selectivity of the catalytic process.

[0093] Specifically, the difference in the distribution of reduction products between Example 1 and Comparative Example 2 in Table 1 is that the cyclic voltage pulse method is not added in Comparative Example 2 during electrodeposition, and the highest Faraday efficiency of formic acid generated at -1.9V in Example 1 is 88.54%, and the Faraday efficiency of hydrogen is 20.98%. However, the highest Faraday efficiency of formic acid generated at -1.9V in Comparative Example 2 is 25.32%, and the Faraday efficiency of hydrogen is 48.39%. When the first cyclic voltage pulse is not added, no Cu is formed. x S-Cu x O structure, the core-shell structure cannot be formed when the catalyst surface is reconstructed, and there is no S vacancy to provide active sites to adsorb CO2 and transfer electrons, and the conversion rate of formic acid is greatly reduced. The reduction of active sites and the decrease in the proportion of edge sites together lead to the weakening of catalytic activity and the reduction of selectivity.

[0094] Specifically, attached Figure 1 , Attachment Figure 2 and attached Figure 3 Description: The core-shell structure can be evenly dispersed into the copper-based catalyst using the cyclic voltage pulse and constant voltage method. The elements in the sample are evenly distributed, and no local enrichment or deficiency is observed. The element content in different regions of the sample fluctuates slightly and has good uniformity. This shows that this preparation method can effectively control the composition and distribution of the catalyst, which is beneficial to the improvement of catalyst performance. At the same time, the uniform distribution of elements reduces the risk of local overreaction or corrosion, thereby improving the service life and stability of the catalyst.

[0095] Specifically, attached Figure 4 The following is a SEM image of the catalyst prepared using the cyclic voltage pulse method. Figure 5 This is a SEM image of the catalyst prepared using the cyclic pulse voltage method coupled with the constant potential method. Figure 4 The preparation method shows a sheet-like stacking structure; Figure 5 The preparation method shows a nanoparticle structure; by comparing the morphology of the catalysts prepared by the two different methods, the attached Figure 5 The surface morphology of the prepared catalyst has a loose porous structure with dense stacking, which means that the sample has a higher density and better structural stability. It also has a larger surface active area and a higher specific surface area, thereby expanding the three-phase interface area, which is beneficial to the adsorption, conduction and diffusion of CO2.

[0096] Tests have shown that the catalyst has good catalytic activity and good selectivity for a single product. Compared with the prior art, the raw material source of the present invention is wide, the raw material price is low, the preparation process is simple, and it is conducive to improving the carbon dioxide conversion efficiency. The electrocatalyst can act on the cathode in the electrochemical reduction reaction of carbon dioxide.

Claims

1. A sulfur-modified electrode for electrochemical reduction of carbon dioxide, characterized in that: The core-shell structure Cu2O-Cu2S-Cu(V) / Cu was in situ deposited and grown on the surface of the copper substrate by electrochemical pulse deposition and electrochemical constant potential deposition reconstruction technology. x O-Cu x S / CM catalyst; During the growth process, CuO-CuS is first deposited on the substrate surface; Then, the electrochemical constant potential deposition reconstruction technique was used to deposit and reconstruct the prepared catalyst, and the Cu x O and Cu x S is reduced and reconstructed, and Cu2O-Cu2S grows on the surface to form a sulfur-modified electrode.

2. A method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide, characterized in that: The method for preparing the sulfur-modified electrode for electrochemical reduction of carbon dioxide according to claim 1 comprises the following steps: S1: soak the copper mesh, copper foam and copper plate substrate in water, 25% hydrochloric acid, ethanol or acetone in turn, clean them by ultrasonic cleaning in an ultrasonic cleaning machine, and then clean and dry them for later use; S2: a mixed solution of bicarbonate, carbonate and sodium sulfide is prepared as an electrolyte, and stirred for 20 minutes under a magnetic stirrer to fully mix, wherein the concentration of sodium bicarbonate and carbonate is 0.1M to 1M, preferably 0.1M to 0.5M; the concentration of sulfur is 0.3mM to 2.0mM, preferably 0.5mM to 1mM; S3: Under the protection of inert gas, the oxidation potential Ea of the cyclic voltage pulse is -0.2V~-0.6V; the reduction potential Ec is -1.2V~-0.6V; The absolute value of the oxidation potential is always set smaller than the absolute value of the reduction potential; The oxidation time Δta is 1 to 5 seconds, preferably 2 to 4 seconds; The reduction time Δtc is 2 to 8 seconds, preferably 4 to 8 seconds; The number of cycles is 50 to 400, preferably 100 to 200; S4: The electrode prepared in step S3 is placed under the protection of an inert gas and reconstructed by electrochemical constant potential in the same electrolyte to reconstruct the surface of the substrate layer by electrodeposition of the catalyst; S5: The electrode prepared in S4 is rinsed clean and dried in a vacuum drying oven at 40-60° C. to prepare a sulfur-modified electrode.

3. The method for preparing a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The concentration of the sodium bicarbonate salt and carbonate salt is 0.1M-1M, preferably 0.1M-0.5M; the concentration of the sulfur is 0.3mM-2mM, preferably 0.5mM-1mM;.

4. The method for preparing a sulfur-modified modified electrode for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The oxidation time Δta in S3 is 1 to 10 seconds, preferably 2 to 4 seconds; The reduction time Δtc is 2 to 8 seconds, preferably 4 to 8 seconds; the number of cycles is 50 to 400 times, preferably 100 to 200 times.

5. The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The molar ratio of the sodium bicarbonate salt or carbonate to sodium sulfide is 117:1 to 200:1, and the preferred molar ratio is 150:1 to 180:

1.

6. The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The sodium bicarbonate salt and carbonate of the electrolyte solution of the cyclic voltage pulse are one or more of KHCO3, NaHCO3, Na2CO3, and K2CO3.

7. The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide according to claim 6, characterized in that: The concentration of the electrolyte is 0.1M-1M, preferably 0.1M-0.5M.

8. The method for preparing a sulfur-modified electrode for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The constant potential method uses a constant voltage method.

9. The sulfur-modified modified electrode for electrochemical reduction of carbon dioxide and the preparation method according to claim 8, characterized in that: The voltage used in the constant voltage method is set to -2.0V to -1.0V, and the deposition time is 800 to 2000 seconds.

Citation Information

Patent Citations

  • Preparation method and application of Cu electrode for electrochemical reduction of carbon dioxide

    CN117026291A

  • Preparation method and application of in-situ growth carbon dioxide electroreduction electrocatalyst

    CN117127207A